Role of musculoskeletal radiology in modern sports medicine - Hynes, J.P.; Walsh, J.; Farrell, T. P.; Murray, A. S.; Eustace, S. J. (Seminars in Muscoloskeletal Radiology, 2018)
Musculoskeletal radiology's role in the recent and continued evolution of sports medicine is an exciting and expanding one. In this article we explore a variety of the ways that musculoskeletal radiology contributes to current practices in modern sports medicine, discussing advances across a variety of imaging modalities in the care of both elite athletes and so-called weekend warriors. We describe the technical and ethical factors pertaining to image-guided therapeutic intervention in athletes and speculate on the potential for future developments in the role of imaging in deciding when an athlete may return to participation. We also explore the recent shift to the delivery of imaging facilities at sporting events and in stadiums.